Efektivitas bimbingan kelompok untuk meningkatkan kemandirian belajar siswa - Nurul Huda Adzkiyah; Tanti Ardianti; Kasmanah Kasmanah (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
the purpose of this study was to determine the effectiveness of group guidance services on the learning independence of grade IX students. The school that is the object of this research is SMP Muhammadiyah 1 Jagakarsa. The type of research used in this research is quantitative pre-experimental research using the one group pre-test and post-test methods. The results of this study indicate that there is an increase in learning independence after being given group guidance services. Sampling in this study were 78 students. From the results of the distribution of the questionnaire, it was found that 10 students had a low level of learning independence, seen from the score on the questionnaire calculation. The normality test of the data was carried out using the one-sample Kolmogorov-Smirnov test. The results of hypothesis testing through the paired sample t-test test showed that Ho was rejected and Ha was accepted, so that it could be concluded that there was an effectiveness of group guidance services on the learning independence of students of SMP Muhammadiyah 1 Jagakarsa class IX.